The influence of mindset on consumer acceptance of products - Loo, Ryner Koh Wee (Nanyang Technological University, 2020)
Idealistic and pragmatic mindsets cause consumers to focus on different aspects of decision-making—the tradeoff between values and practicality. We propose that brand logos are able to activate idealistic and pragmatic mindsets, which influence consumers’ acceptance of a product, and that this relationship is moderated by the level of privacy invasion. Our results suggest that the chosen brand logo primes were unable to activate idealistic and pragmatic mindsets. However, when privacy invasion was high, participants were more accepting of the product if they perceived the brand primes as idealistic compared to pragmatic. Results highlight the importance of brand perceptions in consumer decision-making processes.